The Effect of Health Sector Spending, Education and per Capita Income on Life Expectancy in Indonesia - Yunisvita; Toberliansyah Kholillullah, Kevin; Bashir, Abdul (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2023)
This study aims to determine the effect of government expenditure in the health sector, government expenditure in the education sector, and per capita income on life expectancy in Indonesia. This type of research is quantitative. The data used is secondary data sourced from the World Bank. The analysis technique used is time series data regression analysis using autoregressive distributed lag (ARDL). The scope of the study used Indonesian data for 20 years from 2000-2019. Life expectancy variables as dependent and health sector expenditure variables, education and per capita income as independent The results showed that health sector expenditure had a significant and positive effect on long and short term life expectancy, education sector spending for the short term had a significant and positive effect on certain periods and the long term had a significant and negative effect on life expectancy, Negative and insignificant short-term per capita income has a negative and significant influence on life expectancy.